Influence of chronically altered thyroid status on the activity of liver mitochondrial glycerol-3-phosphate dehydrogenase in female inbred lewis rats - Rauchová, H; Zacharová, G; Soukup, T (Hormone and metabolic research, 2004)
The activity of liver mitochondrial flavoprotein-dependent glycerol-3-phosphate dehydrogenase (GPDH) is considered a reliable marker of thyroid status in acute and short-lasting experiments. The aim of this study was to ascertain whether GPDH activity could also be used as an index of thyroid status during chronic experiments over several months. We therefore analyzed GPDH activity in liver mitochondria of female inbred Lewis rats with thyroid status altered for 2 to 12 months. Hyperthyroid state was maintained by triiodothyronine (T (3)) or thyroxine (T (4)) administration, while methimazole was employed for inducing hypothyroidism. We found a seven- and three-fold increase of GPDH activity in female rats after T (3) or T (4) administration, respectively, compared to euthyroid females (8.9 +/- 2.3 nmol/min/mg protein), whereas administration of methimazole reduced the enzyme activity almost to one-third of the euthyroid values. These changes were not significantly influenced by the duration of hyperthyroid or hypothyroid treatment. We conclude that the level of the rat liver GPDH activity could serve as a useful marker for evaluation of hyperthyroid and hypothyroid status in chronic long-lasting experiments on female inbred Lewis rats.
Keywords: Glycerolphosphate Dehydrogenase; trijodthyronin; Rats, Inbred Lew; methimazol; Mitochondria, Liver; Female; Thyroid Gland; Triiodothyronine; Hypothyroidism; krysa rodu Rattus; Thyroxine; zvířata; štítná žláza; jaterní mitochondrie; hypotyreóza; ženské pohlaví; glycerolfosfátdehydrogenasa; potkani inbrední LEW; Hyperthyroidism; thyroxin; Rats; Animals; hypertyreóza; Methimazole